Ms Glow Strategy After PS Glow Lawsuit Regarding Trademarks - Alamsyah, Azzahra; Nurdiana, Dina; Nur Januarizky, Fira (PT Literasi Nusantara Publisher, 2023)
The PS Glow brand bears a resemblance to the MS Glow brand name. Because the trademark owner MS Glow felt aggrieved, the trademark owner reported to the authorities on charges of using the trademark without permission. In that case, it has been proven that there is a registration without good faith carried out by PS Glow. PS Glow brand registration was made in 2021 after the MS Glow brand became known to the general public. The operation of the cosmetics factory or Skincare under the name